A global estimate of the full oceanic 13C Suess effect since the preindustrial. Issue 3 (6th March 2017) - Eide, Marie; Olsen, Are; Ninnemann, Ulysses S.; Eldevik, Tor
Abstract: We present the first estimate of the full global ocean 13 C Suess effect since preindustrial times, based on observations. This has been derived by first using the method of Olsen and Ninnemann (2010) to calculate 13 C Suess effect estimates on sections spanning the world ocean, which were next mapped on a global 1° × 1° grid. We find a strong 13 C Suess effect in the upper 1000 m of all basins, with strongest decrease in the subtropical gyres of the Northern Hemisphere, where δ 13 C of dissolved inorganic carbon has decreased by more than 0.8‰ since the industrial revolution. At greater depths, a significant 13 C Suess effect can only be detected in the northern parts of the North Atlantic Ocean. The relationship between the 13 C Suess effect and the concentration of anthropogenic carbon varies strongly between water masses, reflecting the degree to which source waters are equilibrated with the atmospheric 13 C Suess effect before sinking. Finally, we estimate a global ocean inventory of anthropogenic CO2 of 92 ± 46 Gt C. This provides an estimate that is almost independent of and consistent, within the uncertainties, with previous estimates. Key Points: The first observationally based estimate of the full global ocean 13 C Suess effect over the industrial era The 13 C Suess effect is strongest in recently ventilated waters; however, its relationship to Cant varies between water masses A global ocean inventory of anthropogenic CO2 of 92 ± 46 Gt C is estimated